Disparate effects of PEG or albumin based surface modification on the uptake of nano- and micro-particles. (21st January 2019) - Sharma, Preeti; Sen, Devashish; Neelakantan, Varsha; Shankar, Vinidhra; Jhunjhunwala, Siddharth
Abstract : Surface modification with PEG or albumin reduces phagocytic internalization of nano-particles but not micro-particles. Abstract : Surface modification of particulate systems is a commonly employed strategy to alter their interaction with proteins and cells. Past studies on nano-particles have shown that surface functionalization with polyethylene glycol (PEG) or proteins such as albumin increases circulation times by reducing their phagocytic uptake. However, studies on surface functionalized micro-particles have reported contradictory results. Here, we investigate the effects of surface functionalization using polystyrene particles with 4 different diameters ranging from 30 nm to 2.6 μm and coating them with either albumin or PEG. Our results show that with increasing particle size, surface functionalization has less to no effect on altering phagocytic uptake. The data also suggest that these differences are observed with a dense arrangement of molecules on the surface (dense brush conformation for PEG conjugation), appear to be independent of the serum proteins adsorbing on particle surfaces, and are independent of the endocytic uptake pathway. These results provide insight into the differences in the ability of surface modified nano- and micro-particles to avoid phagocytic uptake.